The Relationship Between Suicidal Ideation and Cognitive Distortion Among Undergraduates - Tan, Yao Xiong (2020)
Suicide has become a debilitating issue. Although it is a preventable condition but failure to understand the thinking pattern could significantly dampen the effort to avert it. Despite being an important issue, there is still a lack of study centralising into the thinking pattern when suicidal thoughts are mooted in. Due to this gap, this study was set to examine the relationship between cognitive distortion and suicidal ideation. Using purposive sampling 414 students whose were seeking career advice were recruited to participate in this study. Results indicated that there was a significant relationship between cognitive distortion and suicidal ideation. Using multiple regression, the finding showed that out of 10 thinking patterns, overgeneralisation contributes the most to the suicidal thoughts. These findings will help professionals to understand better the nature of suicidal ideation and assist them in providing better services and alleviating its symptoms. This study also discussed the limitations and the directions for future research